STUDI PELAYANAN DAN FASILITAS TERMINAL PENUMPANG BANDAR UDARA DI IBUKOTA PROVINSI KALIMANTAN UTARA - Achmad Zultan Mansur; Budi Setiawan; Khayrunisyah Yahya (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
North Kalimantan Province has only one domestic airport in the city of Tanjung Selor called Tanjung Harapan. Therefore the standard of services and facilities provided by the airport management must be in accordance with standards that are able to create a comfortable and conducive atmosphere. This research uses descriptive analysis method and IPA (Importance Performance Analysis) analysis method, in this analysis there are 36 attributes or indicators that serve as a benchmark in determining passenger satisfaction with services provided at Tanjung Harapan airport terminal. The purpose of this study is to determine the standard level of passenger terminal services and determine the level of passenger satisfaction with airport terminal services. The results of research on Terminal Services Standards According to PM. Number 178 of 2015 states that the results of the assessment of the facilities of the departure and arrival process scored 75 with the title "B" (very good). The IPA (Importance Performance Analysis) method on passenger satisfaction there are 5 attributes in quadrant I (top priority), 17 attributes in quadrant II (maintain performance), 10 attributes in Kudran III (low priority), and 4 attributes in quadrant IV (excessive).